IMPROVING STUDENTS’ ACTIVITY AND CONCEPTUAL UNDERSTANDING BY AN IMPLEMENTATION OF PHYSICS INTERACTIVE MULTIMEDIA-ASSISTED GROUP INVESTIGATION MODEL - I Putu Tedy Indrayana; Gusti Ayu Rai Tirta (Jurnal Pendidikan Fisika Undiksha, 2022)
Conceptual understanding is the main competency that must be possessed by students when participating in physics learning. This study aims to improve students' learning activity and conceptual understanding of physic in class XA Pharmacy at SMK Bintang Persada Denpasar on the subject of Elasticity and Static Fluid through online group investigation. This learning uses PhIMP (Physics Interactive Multimedia Packaging). PhIMP-assisted online group investigation is unique because students learn comprehensively and deeply about basic physics concepts through online experimental activities, group discussions, and online presentations. This research was a classroom action research that involved 31 students. It was implemented in two cycles. Student’s learning activity and conceptual understanding is a variable studied. The instruments used a conceptual understanding test that consists of 30 items and a learning activity observation sheet. The data were collected using pre-test and post-test technique in each learning cycle. The results indicate that there is an increase in student learning activities from cycle I to cycle II. The average score of student learning activities for the cycle I and cycle II were 35.5 and 48.5, respectively. There is an improvement in student’s conceptual understanding. The N-gain scores in cycle I and cycle II were 0.39 and 0.71. There is also an improvement in the dimensions of conceptual understanding abilities. These results indicate that theinteractive multimedia-assisted group investigation model is powerful to facilitate students in improving their activity and conceptual understanding.